2015
DOI: 10.1016/j.neuroimage.2015.07.047
|View full text |Cite
|
Sign up to set email alerts
|

Brains striving for coherence: Long-term cumulative plot formation in the default mode network

Abstract: Many everyday activities, such as engaging in conversation or listening to a story, require us to sustain attention over a prolonged period of time while integrating and synthesizing complex episodic content into a coherent mental model. Humans are remarkably capable of navigating and keeping track of all the parallel social activities of everyday life even when confronted with interruptions or changes in the environment. However, the underlying cognitive and neurocognitive mechanisms of such long-term integra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 47 publications
3
36
0
Order By: Relevance
“…Accordingly, in this functional magnetic resonance imaging (fMRI) study we established the brain regions and networks that support time-extended semantic integration (formation of the semantic gestalt), as well as those that are sensitive to changes in semantic context (update of the semantic gestalt). Importantly, in doing so we provide some timely evidence that bridges the existing work on narratives (Hasson et al, 2008;Lerner et al, 2011;Simony et al, 2016;Tylen et al, 2015) with the broader neurocognitive theories of semantic cognition .…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Accordingly, in this functional magnetic resonance imaging (fMRI) study we established the brain regions and networks that support time-extended semantic integration (formation of the semantic gestalt), as well as those that are sensitive to changes in semantic context (update of the semantic gestalt). Importantly, in doing so we provide some timely evidence that bridges the existing work on narratives (Hasson et al, 2008;Lerner et al, 2011;Simony et al, 2016;Tylen et al, 2015) with the broader neurocognitive theories of semantic cognition .…”
Section: Introductionmentioning
confidence: 80%
“…Other studies, instead, have measured multi-item semantic combinations without task manipulations that distinguish between brain structures involved in semantic integration (or formation of the semantic gestalt) from those involved in extrasemantic neurocomputations (e.g., working memory (WM), attentional control, etc. : e.g., (Hasson et al, 2008;Lerner et al, 2011;Simony et al, 2016;Tylen et al, 2015). Accordingly, in this functional magnetic resonance imaging (fMRI) study we established the brain regions and networks that support time-extended semantic integration (formation of the semantic gestalt), as well as those that are sensitive to changes in semantic context (update of the semantic gestalt).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hypothetical slow process is effectively an extension of working memory, integrating episodic and semantic content over longer spans of time in order to guide long-term patterns of behavior across changing contexts. Neuroimaging studies suggest that narrative synthesis is mediated by major hubs of the DMN, including the medial prefrontal cortex, posterior cingulate/precuneus, and temporo-parietal junction, which integrate multisensory information across medium-to-long spans of time (Tylen et al, 2015;Lerner et al, 2011 The emergence and development of ToM, MTT, and the "slow process" of narrative synthesis all reflect a more basic cognitive shift in the nature of representation, from concrete to abstract (Donald, 1991;Deacon, 1997). The objects of cognition are no longer bound to physical referents in the present situation, but include counterfactual worlds and abstract concepts that can be shared through language.…”
Section: Event Cognition In Evolutionary Perspectivementioning
confidence: 99%
“…In these studies, brain activity is examined during processing of a stream of audio or film clips, from which the content of temporally separate clips can be meaningfully integrated into a coherent sequence of events. One such study [48] found that activity in the PM network was higher in magnitude during processing of coherent audio clips when compared with clips that did not comprise a coherent sequence of events (incoherent). Milivojevic et al [49] compared brain activity patterns as participants watched a continuous movie in which odd-numbered and even-numbered scenes depicted two different coherent narratives involving the same characters and spatial contexts.…”
Section: Temporal Structure In Complex Lifelike Eventsmentioning
confidence: 99%